Analysis Comparative of Performance Optimization Techniques for PHP Framework Testing: Laravel, CodeIgniter, Symfony: Analisis Perbandingan Teknik Optimasi Performa Untuk Pengujian Framework PHP: Laravel, CodeIgniter, Symfony - Fauzan Prasetyo Eka Putra; Achmad Zulfikri; Abd Rohman; Royfal Alim (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Web application performance significantly impacts digital services in sectors like e-commerce, education, and healthcare, where poor response time (>100 ms) can reduce user satisfaction by up to 20% and cause revenue losses. Despite numerous studies on PHP frameworks, comprehensive comparisons integrating optimization techniques remain limited. This research empirically evaluates the performance of Laravel, CodeIgniter, and Symfony, focusing on response time, throughput, and error rate before and after applying optimization techniques. Load and stress testing was conducted using Apache JMeter, Xdebug, and New Relic on a student management system with a MySQL database (10,000 records), simulating realistic scenarios from 1 to 100 users, mimicking e-commerce or educational platforms. Optimization techniques included caching (e.g., route caching in Laravel, query caching in CodeIgniter), database optimization (indexing, eager loading), and code refactoring. Results revealed CodeIgniter achieved the lowest response time (16.49 ms, 41.4% reduction) and highest throughput, ideal for lightweight applications like news portals. Laravel showed the greatest improvement under high load (35.1% reduction, from 118.34 ms to 76.80 ms), suitable for e-commerce platforms. Symfony demonstrated stable performance (20.0%–25.0% reduction), fitting enterprise applications with complex APIs. This study provides practical guidance for developers in selecting PHP frameworks based on project requirements and offers optimization recommendations to enhance web application efficiency and scalability.